2008
DOI: 10.1007/s11664-008-0548-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Aluminum Concentration on the Interfacial Reactions of Sn-3.0Ag-xAl Solders with Copper and ENIG Metallizations

Abstract: Aluminum was added into Sn-3.0Ag (wt.%) solder to investigate the effect of aluminum concentration on the interfacial reaction of Sn-3.0Ag-xAl solders with copper or electroless nickel immersion gold (ENIG) metallizations. Four different Sn-3.0Ag-xAl solders (x = 0 wt.%, 0.1 wt.%, 0.5 wt.%, and 1.0 wt.%) were used for comparison. It was found that the composition, morphology, and thickness of interfacial reaction products were strongly dependent on aluminum concentration. At low aluminum concentration (0.1 wt.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…In a study by Jee et al, 11,12 the Al-Cu IMC appeared at the solder/substrate interface rather than in the solder. In the present study, due to the limited solder volume, Al was quickly depleted while forming the Al-Cu IMC, and Cu 6 Sn 5 forms at the solder/substrate interface.…”
Section: Liquid-and Solid-state Reactions In the Sn-ag-al/cu And Sn-amentioning
confidence: 92%
See 1 more Smart Citation
“…In a study by Jee et al, 11,12 the Al-Cu IMC appeared at the solder/substrate interface rather than in the solder. In the present study, due to the limited solder volume, Al was quickly depleted while forming the Al-Cu IMC, and Cu 6 Sn 5 forms at the solder/substrate interface.…”
Section: Liquid-and Solid-state Reactions In the Sn-ag-al/cu And Sn-amentioning
confidence: 92%
“…Traditionally trace amounts of certain elements, i.e., rare-earth elements, have proven to be effective in suppressing the growth of Cu-Sn IMC layers and consequently improved longterm reliability of the solder joint. 9 Recently, several researchers [9][10][11][12][13][14][15] have demonstrated that the addition of small quantities of Al or Zn can suppress Cu-Sn IMC layer growth.…”
Section: Introductionmentioning
confidence: 99%
“…In Cu-containing solders or during soldering to Cu substrates, Al additions usually cause one or more CuxAly intermetallics to form. Four Cu-Al intermetallics have been reported in solders, θ-CuAl2, η2-CuAl, δ-Cu33Al17 and 1-Cu9Al4, depending on the base solder, Al addition and substrate as summarised in Table 1 [5,6,[8][9][10][11][12][13][14][15][16][17][18]. It can be inferred from Table 1 that, for Sn-Ag-Cu solders solidified without reactive substrates, CuAl2 is observed at Al levels above ~1wt% [12] while CuAl is found at Al levels between 0.1-1wt% [13,18], and that the situation is more complex during soldering to Cu substrates due to substrate dissolution.…”
Section: Introductionmentioning
confidence: 99%
“…The addition of aluminum has attracted much interest in recent years. Research on Al addition as nanoparticles or minor alloying element has been reported [ 12 , 13 , 14 , 15 , 16 , 17 , 18 ]. Amagai [ 12 ] observed that the addition of 0.05% Al nanoparticles did not have any significant effect on the interfacial IMC.…”
Section: Introductionmentioning
confidence: 99%
“…Amagai [ 12 ] observed that the addition of 0.05% Al nanoparticles did not have any significant effect on the interfacial IMC. As for the addition of aluminum as minor alloying element, a few works on the effect of Al on the mechanical properties, microstructure and solder/Cu substrate interfacial reaction have been reported [ 2 , 9 , 11 , 14 , 15 , 16 , 17 , 18 ]. Previous studies have shown that minor addition of Al gives promising results in suppressing undercooling of β-Sn and reduced formation of brittle phase Ag 3 Sn in SAC solder matrix [ 14 ].…”
Section: Introductionmentioning
confidence: 99%